SYNTHESIS OF A SPECIAL TYPE OF ZEOLITE FROM ANALCIME FAMILY WITH TRIETHANOLAMINE AND ITS CHARACTERIZATION WITH XRD, FTIR AND SEM (Journal of Sciences, Islamic Republic of Iran)
A type of zeolite from the analcime family was prepared by using triethanolamine, silica gel and sodium aluminate. The average particle size was around 24 µm. FTIR, XRD and SEM results approved the type of zeolite which was formed